Preventive risk analysis in the maintenance of patency of the peripherally inserted central catheter - Antônio Fernandes Costa Lima; Amanda Saba; Simone Berger; Silvia Sauaia Bianchini; Fernando Tobal Berssaneti
ABSTRACT This theoretical and reflexive study analyzed the risks related to the maintenance of patency of the Peripherally Inserted Central Catheter with the use of saline solution in comparison with saline-filled syringes, through the application of the Healthcare Failure Mode and Effect Analysis - HFMEA. The process was mapped, detailing the failure modes of each step. For the calculation of the Risk Priority Number, the severity and probability of the failure modes were analyzed. This analysis gave rise to the severity and probability matrix. Finally, actions to reduce the failure modes in the maintenance of patency were proposed, considering the use of saline-filled syringes in comparison to the use of saline ampoules. It was verified that the use of saline ampoules is associated with a greater risk, since it requires four stages more than saline-filled syringe does not, increasing the risk of contamination and the level of three different risks, which would result in additional hospital costs. The use of the saline-filled syringe would avoid risks that could negatively affect the patient's health, the nursing professional and the health institution.